The Effect of Application of Discharge Planning Seci Model on The Completeness of Discharge Planning Documentation for Tuberculosis - Ayu Afriani Panyuwa; Luky Dwiantoro; Muhammad Rofi'i (Poltekkes Kemenkes Jakarta III, 2023)
Background: The implementation of discharge planning must be documented completely. Preliminary study found that 90% of discharge planning implementation is not documented. The weakness of the intervention that has been done by previous researchers is that it does not focus on increasing the completeness of documentation, especially on the documentation of discharge planning, the application of discharge planning based on knowledge management SECI model as an intervention applied to improve the completeness of documentation on discharge planning. Objectives: The purpose of this study was to determine the effect of discharge planning based on knowledge management SECI model on the completeness of documentation of discharge planning for tuberculosis. Methods: This research is quantitative research with quasi-experimental approach with post-test only design with nonequivalent control group. The number of samples was 34 medical records with a diagnosis of pulmonary TB, each of which consisted of 17 samples in the control group and 17 samples in the intervention group. The intervention in this research is the implementation of discharge planning based on knowledge management SECI model. The data were taken using the discharge planning SECI model observation sheet and the documentation completeness observation sheet which had been tested by expert and analyzed using the Mann-Whitney test. Results: The results showed p value is 0.000 < 0.05. Conclusion: Application of discharge planning based on knowledge management SECI model has a significant effect on the completeness of documentation of discharge planning for tuberculosis (TB). Nurses must become to manage knowledge, good time management, and be a role model in providing nursing care.